Performance in Principal-Agent Dyads: The Causes and Consequences of Perceived Asymmetry of Commitment to the Relationship - Ross, William T.; Anderson, Erin; Weitz, Barton (Management Science, 1997)
We focus on the principal-agent relationship in a distribution channel. In a services context (insurance), we examine how two facets of performance, from the point of view of both the principal and the agent, are influenced by the perceiver's belief that it is more committed to the relationship than is the other party. Using primary data from 255 insurance agent-insurance provider dyads, we show that each side's assessment of how much it benefits from the dyad is related in a potentially dysfunctional manner to its perception of asymmetric commitment. Perceivers rate their performance outcomes from the dyad (i.e., harmony and profit) highest when they believe they are less committed than their counterpart. Conversely, they rate their own performance outcomes lowest when they believe they are more committed than the other party. We explain this finding in terms of suspected opportunism and offer a partial test of this explanation compared with explanations from theories of equity and power/dependence. Further, we demonstrate that each party's perception of asymmetric commitment partially reflects actual asymmetry, as measured by confidential data collected from both sides. Perceived asymmetric commitment is also shown to be related to levels of communication and dependence in the dyad. Managerial implications for reducing perceived asymmetric commitment and improving the performance outcomes of each dyad member are discussed.